Interaksi Nitrogen dengan Insidensi Penyakit Tungro dan Pengedaliannya Secara Terpadu pada Tanaman Padi - Wasis Senoaji; R. Heru Praptana (Iptek Tanaman Pangan, 2013)
Nitrogen (N) is a major nutrient for rice plant growth. To increase rice productivity, the use of superior variety is a key factor on rice production in Indonesia. The superior rice variety generally has a high response to N fertilizer, therefore deficiency of N becomes the limiting factor for the rice growth and yield. The problem arises when the application of N nutrient to achieve high productivity was only based on the recommended fertilizer dosage or yield target without considering the safety of rice from pests and diseases. Tungro is an important disease in rice which is affected by the rate of N. Tungro is caused by the interaction between two different viruses, namely Rice tungro bachiliform virus (RTBV) and Rice tungro spherical virus (RTSV), both are transmitted by green leafhopper. The tungro disease incidence is the result of interaction between plants, tungro virus, vector and environment, where the use of N fertilizer influences the dynamics of viral tungro disease. Interaction of plant N with green leafhoppers affects the increased fitness of insects. Interaction of plant N with viruses changes the cell metabolism, resulting in the changing of chloroplast morphology and an increased rate of respiration, which stimulates absorption of nutrients as the material for synthesis of protein. Fertilizer management should be part of the synergy between soil fertility management and integrated pest management (IPM) to create a healthy crop and environment. Fertilizer management should be synergistically integrated with other crop management components to support the defense mechanism of plants against pests and diseases. Three N management strategies to control tungro disease, including: 1) suitability of N type; 2) accuracy of N quantity based on the diagnosis and 3) the timeliness of application. These strategies should be considered, especially in the endemic tungro area.